Canagliflozin Attenuates Hepatic Steatosis and Atherosclerosis Progression in Western Diet-Fed ApoE-Knockout Mice - Zuo Q; Zhang G; He L; Ma S; Ma H; Zhai J; Wang Z; Zhang T; Wang Y; Guo Y (Drug Design, Development and Therapy, 2022)
Qingjuan Zuo,1,2 Guorui Zhang,1,3 Lili He,2 Sai Ma,4 Huijuan Ma,5 Jianlong Zhai,6 Zhongli Wang,7 Tingting Zhang,2 Yan Wang,2 Yifang Guo1,2 1Department of Internal Medicine, Hebei Medical University, Shijiazhuang, People’s Republic of China; 2Department of Geriatric Cardiology, Hebei General Hospital, Shijiazhuang, People’s Republic of China; 3Department of Cardiology, the Third Hospital of Shijiazhuang City Affiliated to Hebei Medical University, Shijiazhuang, People’s Republic of China; 4Department of Internal Medicine, Hebei General Hospital, Shijiazhuang, People’s Republic of China; 5Department of Endocrinology, Hebei General Hospital, Shijiazhuang, People’s Republic of China; 6Department of Cardiology, Hebei General Hospital, Shijiazhuang, People’s Republic of China; 7Department of Physical Examination Center, Hebei General Hospital, Shijiazhuang, People’s Republic of ChinaCorrespondence: Yifang Guo, Department of Geriatric Cardiology, Hebei General Hospital, No. 348, Heping West Road, Xinhua District, Shijiazhuang, Hebei, 050051, People’s Republic of China, Tel +86-15100189182, Email guoyifang@hotmail.comPurpose: To investigate the effect of canagliflozin (20 mg/kg) on hepatic steatosis and atherosclerosis, and further to explore its possible mechanism.Methods: Blood glucose, blood lipid, oxidative stress response and inflammatory cytokines were examined by intraperitoneal glucose tolerance test and ELISA assay. HE and Oil Red O staining were used to estimate the extent of hepatic steatosis and atherosclerosis. RNA-seq and qRT-PCR were used to further investigate the potential mechanism. The effects of canagliflozin on autophagy were detected using transmission electron microscopy and Western blotting. The endothelial function-related markers were determined by qRT-PCR.Results: Canagliflozin notably alleviated the elevation in blood glucose and insulin resistance in western diet-fed ApoE-/- mice. In ApoE-/-+Cana group, ApoE-/- mice had lower levels of TG, TC, LDL-C, TNF-α, IL-6, IL-1β, and MCP-1. HE and Oil Red O staining presented that canagliflozin restrained the atherosclerotic plaque development and lipid accumulation. RNA-seq showed that 87 DEGs were relevant to improvement of hepatic steatosis and atherosclerosis by canagliflozin. Among them, CPS1, ASS1, ASL, ARG1, MATLA, GLS2, GOT1, SREBP1, Plin5, Retreg1, and C/EBPβ were verified. KEGG enrichment analysis indicated that DEGs were mainly involved in amino acid metabolism. Besides, we observed that canagliflozin reduced the contents of aspartic acid and citrulline in liver. Western blotting showed that ASS1 and p-AMPK/AMPK was remarkably elevated after administration of canagliflozin. Correspondingly, canagliflozin down-regulated SREBP1, FAS, ACC1, HMGCR, p-mTOR/m-TOR, p-ULK1/ULK1 and p62, but up-regulated CPT1, Beclin 1 and LC3 II/LC3I. TEM showed that canagliflozin reduced the number of lipid droplets and increased the autophagosomes. Moreover, we found that canagliflozin elevated the aortic endothelial function-associated markers including ASS1, ASL and eNOS.Conclusion: Canagliflozin may attenuate hepatic steatosis by improving lipid metabolism, enhancing autophagy, and reducing inflammatory response through ASS1/AMPK pathway. Besides, canagliflozin further effectively improves the aortic endothelial function, thereby suppressing atherosclerosis development.Keywords: canagliflozin, hepatic steatosis, atherosclerosis, RNA-seq, dyslipidemia, inflammatory response, autophagy